2001
DOI: 10.1017/s0033291701003774
|View full text |Cite
|
Sign up to set email alerts
|

Verbal self-monitoring and auditory verbal hallucinations in patients with schizophrenia

Abstract: Impaired verbal self-monitoring was evident in both hallucinators and non-hallucinators. As both groups had delusions, the results suggest an association between delusions and impaired judgements about ambiguous sensory stimuli. The specific tendency of hallucinators to misattribute their distorted voice to someone else may reflect impaired awareness of internally generated verbal material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
179
4
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(203 citation statements)
references
References 30 publications
17
179
4
3
Order By: Relevance
“…Clinical observations reveal that schizophrenia is associated with both over-attributions (other-to-self-direction) as well as under-attributions (self-to-other direction). This is also reflected in the schizophrenia literature with respect to speech attribution (Johns et al, 2001, Johns et al, 2006, Stephane et al, 2009) and also with respect to incorrect agency attribution either to external sources or to the self (Daprati, et al, 1997, Fourneret, et al, 2001). In the majority of agency manipulation studies schizophrenia patients showed a tendency similar to that in our study, namely, a…”
Section: Sense Of Agency Deficits In Schizophreniamentioning
confidence: 93%
“…Clinical observations reveal that schizophrenia is associated with both over-attributions (other-to-self-direction) as well as under-attributions (self-to-other direction). This is also reflected in the schizophrenia literature with respect to speech attribution (Johns et al, 2001, Johns et al, 2006, Stephane et al, 2009) and also with respect to incorrect agency attribution either to external sources or to the self (Daprati, et al, 1997, Fourneret, et al, 2001). In the majority of agency manipulation studies schizophrenia patients showed a tendency similar to that in our study, namely, a…”
Section: Sense Of Agency Deficits In Schizophreniamentioning
confidence: 93%
“…Cognitively, language deficits have been identified in children at risk for schizophrenia (Cannon et al, 2002;Fuller et al, 2002;Ott et al, 2001) as well as in patients in their first episode of psychosis (Fuller et al, 2002;Hoff et al, 1999). Numerous neuropsychological and psycholinguistic studies have established that patients with schizophrenia show selective language abnormalities as they monitor the source of verbal input (Ditman and Kuperberg, 2005;Johns et al, 2001), explicitly or implicitly retrieve information from semantic memory [e.g (Goldberg et al, 1998;Minzenberg et al, 2002)], select the appropriate meaning of semantically ambiguous words (Sitnikova et al, 2002;Titone et al, 2000), detect linguistic anomalies within sentences (Kuperberg et al, 2006a;Kuperberg et al, 1998;Kuperberg et al, 2000;Kuperberg et al, 2006b) and parse syntactically complex sentences (Condray et al, 1996) [for reviews, see (Kuperberg and Caplan, 2003;Kuperberg and Goldberg, 2006)]. Functional imaging studies report both abnormal increases and decreases in the recruitment of the left inferior prefrontal gyrus in schizophrenia during semantic tasks including encoding (Kubicki et al, 2003;Ragland et al, 2004), retrieval (Weiss et al, 2003) and priming (Kuperberg et al, 2007), although abnormal function in this region is not usually seen in isolation, but rather in association with abnormal modulation of other language regions including superior, inferior and medial temporal cortices.…”
Section: Functional Significance Of Abnormalities In Broca's Areamentioning
confidence: 99%
“…Johns et al [8] assessed verbal self-monitoring in patients with schizophrenia who heard voices and had delusions (hallucinators). We induced verbal self-monitoring by manipulating auditory verbal feedback while participants spoke out loud, thus introducing a disparity between what individuals expected to hear and what they actually perceived.…”
Section: Introductionmentioning
confidence: 99%